Effect of hand hygiene intervention on the absenteeism of pre-school children in Klang Valley, Malaysia: a quasi-experimental study - Nurul Azmawati Mohamed @ Abd Aziz; Mohd Dzulkhairi Mohd Rani; Zarini Ismail; Tengku Jamaluddin T.Z.M.; Ramli S.; Faroque H.; Abd Samad F.N.; Ariffien A.R.; Che Amir Farid A.A.R.; Isahak I. (Institute of Pediatrics of Zhejiang University, 2024)
Indexed by Scopus/ERA